Mouse's first Halloween - Thompson, Lauren, 1962- (Simon & Schuster Books for Young Readers, 2000)
"One spooky night in the fall, Mouse creeps out and hears bats flying flit! flit! flit! and apples dropping plop! plop! plop! and children singing 'trick or treat!' What could it be?"